SOCIO- MEDICAL ORIENTATION VARIATIONS AMONG URBAN AND RURAL POPULATION - M Mohseni; F Shafii (Tehran University of Medical Sciences, 1977)
This study examined the relationship between some socio- demographic variables, medical orientations and utilization of health services of urban in comparison with rural head of households. The data for this study were obtained as part of 1975 health survey of the southern provinces of Iran. The finding revealed a significant relationship between the indices used in this study, particularly in the urban sample. Favorable attitudes toward modern medicine were more likely to occur in the urban population where more formal and informal education helps to create new habits, and consequently the acquisition of a new health attitude.